Modelling Of An Educational Gas Turbine System And Controller Design Using LMS Algorithm - Aidil Azwin Bin Zainul Abidin (2023)
Gas trubines are used extensively in generation due to the ability to pick up load faster than any oyher thermal methods for this reason a control method for it is very important. Presently the control of gas turbine power plants use a fixed point Proportional, Differential and Intergral (PID) controller.